Experimental investigation of forming forces in frictional stir incremental forming of aluminum alloy AA6061-T6 - Baharudin, B. T. Hang Tuah; Azpen, Qasim Mhalhal; Sulaiman, Shamsuddin; Mustapha, Faizal (MDPI, 2017)
The incremental sheet forming (ISF) process is an emerging flexible sheet-forming process, which is adequate for the manufacturing of unique or small-volume batches. Single-point incremental forming (SPIF) is the original technology of incremental sheet-forming processes. In this article, frictional stir-assisted SPIF was used to deform AA6061-T6 aluminum alloy. Experimental tests were conducted to measure the forming forces during this process for the concerned lightweight material. The influence of process parameters was investigated, which included tool rotation speed, feed rate, step size and tool diameter on the produced forming forces. A Taguchi technique for the design of experiment (DOE) and the varying wall angle conical frustum (VWACF) test was employed in this study. The results show that the rotation spindle speed was the most dominant parameter that affects the forming forces, followed by the step size, feed rate and tool diameter. In addition, the interaction between the feed rate and step size has a notable impact on the values of the forming forces.